2019
DOI: 10.3389/fninf.2019.00074
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Movement From Electrocorticographic Activity: A Review

Abstract: Electrocorticography (ECoG) holds promise to provide efficient neuroprosthetic solutions for people suffering from neurological disabilities. This recording technique combines adequate temporal and spatial resolution with the lower risks of medical complications compared to the other invasive methods. ECoG is routinely used in clinical practice for preoperative cortical mapping in epileptic patients. During the last two decades, research utilizing ECoG has considerably grown, including the paradigms where beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 199 publications
(391 reference statements)
2
52
0
Order By: Relevance
“…State-of-the-art EEG-based BMIs boosted by deep-learning methods have proven to be feasible for multidirectional 3D robotic arm control, with success rates of about 60% [132]. Even the more invasive methods, such as ECoG, hardly surpass the 80% success rate in 2D cursor control tasks [133]. Although these are impressive results with a wide range of practical applications, BCVs require stable, high success rates.…”
Section: A State-of-the-artmentioning
confidence: 99%
“…State-of-the-art EEG-based BMIs boosted by deep-learning methods have proven to be feasible for multidirectional 3D robotic arm control, with success rates of about 60% [132]. Even the more invasive methods, such as ECoG, hardly surpass the 80% success rate in 2D cursor control tasks [133]. Although these are impressive results with a wide range of practical applications, BCVs require stable, high success rates.…”
Section: A State-of-the-artmentioning
confidence: 99%
“…This electrode configuration is not optimised for LFP recordings as it has been shown that the properties and decoding performance of LFP signals depend on the recording electrode depth [41,49]. There is also increasing interest in using surface contact electrodes for BMI applications which offer adequate spatio-temporal resolution and less traumatic for the brain tissue [50,51]. Analyses on the impact of referencing scheme on the decoding performance from these types of electrodes are out of scope of our present study and can be potential direction for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the incidence rate of of beta bursts in the primary somatosensory cortex is inversely correlated with the ability to detect tactile stimuli [24] and also affects other motor functions. Intracranial recordings, such as ECoG, allow reliable measurement of the faster gamma band activity, which is temporally and spatially specific to movement patterns [26] and is thought to accompany movement control and execution. Overall, based on the very solid body of research, rhythmic components of brain sources, s(t), appear to be useful for BCI implementations.Given the linearity of the generative model ( 1), these rhythmic signals reflecting the activity of specific neuronal populations can be computed as linear combinations of narrow-band filtered sensor data x(t).…”
Section: Methodsmentioning
confidence: 99%